Material Consequence and Counter-Factuals - Hitchcock, David (My University, 2013)
A conclusion is a “material consequence” of reasons if it follows necessarily from them in accordance with a valid form of argument with content. The corresponding universal generalization of the argument’s associated conditional must be true, must be a covering generalization, and must be true of counter-factual instances. But it need not be law-like. Pearl’s structural model semantics is easier to apply to such counter-factual instances than Lewis’s closest-worlds semantics, and gives intuitively correct results.
This paper was presented at a conference, Virtues of Argumentation, sponsored by the Ontario Society for the Study of Argumentation, and held at the University of Windsor from May 23-25. It is expected to be published in a CD of the proceedings.
Keywords: associated conditional; closest-world semantics; consequence; counter-factuals; covering generalization; David Lewis; Judea Pearl; law-like generalization; material consequence; structural model semantics; Philosophy; Philosophy